Sustainable Development and Consumer Preferences in Glamping Tourism: A Comprehensive Analysis - Raxmatov Ziyodullo Nosirovich; Umarova Dilfuza Raxmatulla Kizi; Tuychiyev Anvarjon Muxtorjonovich; Jalilov Arslon Xoshimovich; Sharipov Utkir Xikmatullayevich (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
Glamping — a fusion of the words “glamour” and “camping” — represents a modern form of tourism that combines luxury amenities with environmental sustainability. This research aims to explore consumer preferences towards glamping tourism in Uzbekistan and to examine how sustainability factors influence decision-making. Data were collected from 407 respondents via an online survey and analyzed using a logistic regression model. The results indicate that valuing ecology and sustainability significantly increases the likelihood of choosing glamping. Particularly, young adults aged 25–35 and high-income consumers show greater interest in glamping services and are willing to pay more for environmentally friendly options. Based on the findings, it is demonstrated that developing glamping tourism according to sustainable principles can help create new market segments.